Roman Dams in Asia Minor - Lafli, Ergün; Buora, Maurizio (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
In this brief paper we will focus on six dams of the Roman period in Asia Minor, respectively Böğet, Örükaya, Seleucia Pieria, Ancyra, Aezani and Sardis, which are presented here in some outlines. The aim of this article is to introduce these ancient engineering monuments all together.